Psychometric properties of the smartphone addiction scale-short version (SAS-SV) in Honduran university students - Sergio Hidalgo-Fuentes; Isabel Martínez-Álvarez; Fátima Llamas-Salguero; Iris Suyapa Pineda-Zelaya; César Merino-Soto; Guillermo M. Chans (PLoS ONE, 2025)
Problematic smartphone use (PSU) is a global issue associated with numerous adverse outcomes, especially among young people. One of the most widely used instruments to evaluate PSU is the Smartphone Addiction Scale-Short Version (SAS-SV). This study examined the psychometric properties of the Spanish version of the SAS-SV, including factorial validity, convergent validity, divergent validity, and reliability. The final sample comprised 530 students from a university in Honduras. Confirmatory factor analysis provided evidence supporting the validity of the instrument’s internal structure. Reliability was estimated using McDonald’s omega and Cronbach’s alpha coefficients. Convergent validity was assessed through correlations with problematic Internet use, depression, anxiety, and stress. Measurement invariance tests were conducted across sex and age categories. The results indicated that the SAS-SV adequately fits a one-dimensional, reliable model and demonstrated measurement equivalence across groups of sex and age. Finally, the SAS-SV demonstrated a strong correlation with problematic Internet use, depression, anxiety, and stress. These findings support the SAS-SV as a valid and reliable instrument for examining PSU among university students in Honduras.